2021
DOI: 10.1177/0143624421997989
|View full text |Cite
|
Sign up to set email alerts
|

Towards implementing an indoor environmental quality standard in buildings: A pilot study

Abstract: This paper demonstrates the implementation methodology for India’s first IEQ standard (ISHRAE Standard-10001:2016) in actual buildings. The IEQ standard encompasses the definitions of IEQ elements (i.e. thermal comfort, indoor air quality, visual comfort, and acoustic comfort), threshold values of IEQ parameters determining these elements, specifications of measuring instruments, and methodology to undertake IEQ assessments in buildings. The pilot study identified the preliminary findings to understand and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the context of climate change, energy efficiency, and renewable energy, we are looking for novel energy optimisation techniques leading to the identification of designs and technologies that will reduce energy use and maximise energy saving in hot and dry locations (Sansaniwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of climate change, energy efficiency, and renewable energy, we are looking for novel energy optimisation techniques leading to the identification of designs and technologies that will reduce energy use and maximise energy saving in hot and dry locations (Sansaniwal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air quality can be compromised by both outdoor and indoor sources of pollutants related to building materials, equipment, animals and humans ( Van Tran et al, 2020). Recent research has demonstrated new implementation methodologies for quantifying IEQ elements (i.e., thermal comfort, indoor air quality, visual comfort, and acoustic comfort) in real buildings (Sansaniwal et al, 2021b). Below is a summary of the main findings of the articles included in this Research Topic.…”
mentioning
confidence: 99%